Studi Kerusakan Tanaman Sawi (Brassica sp) dan Selada (Lactuca sativa L) Akibat OPT pada Sayuran Hidroponik di Kota Ambon - Misda Alberto Senen; Christoffol Leiwakabessy; Jacobus S.A. Lamerkabel; Costanza Uruilal (Fakultas Pertanian, Universitas Pattimura, 2022)
Hydroponic vegetables are vegetables that grow with the help of liquids containing mineralsnecessary for vegetables to grow. This study aims to inventory the many types of pests that attackmustard and lettuce plants on hydroponic media. This research was conducted in two locations,namely Lateri village and Rumahtiga villages. The types of data collection are in the form ofsurveys, interviews, and also direct observations in the field, which are then processeddescriptively. Observation of pests and diseases can be carried out once a week until the stage ofharvesting. The results of observations from the two research sites obtained the largest numberof individual populations of the order Diptera (Fruit Flies) with 37 heads, followed by the secondhighest number, namely the order Lepidoptera (Moths) with 7 heads, while for the ordersHemiptera and Hymenoptera (Walang sangit and Honey bee) the number was the same, namely2 each